Consumer Preference and Properties of Raw and Cooked Milled Rice - Mundo, Angelita M. Del; Juliano, Bienvenido O. (Wiley, 1981)
Consumer preference tests for raw and cooked rices were run on representative consumers 16 years and older in a selected Philippine village. For four sets of samples, major criteria for selecting raw milled rice were grain whiteness and hardness, and aroma and flavor for boiled rice. Actual preference ranks suggested partiality to white raw rice and low‐amylose, intermediate‐amylose and high‐amylose boiled rice in order of decreasing preference. Soft texture due to low amylose content probably contributed to better flavor of boiled rice.Selection criteria for one set of waxy rices were aroma and whole, big grains for raw rice, and aroma and cohesiveness for rice cake suman sa antala. Properties disliked in suman were flakiness, and coarse, hard, and soft textures. Among five low‐gelatinization temperature, waxy milled rices, the traditional, aromatic, coarse‐grained Malagkit Sungsong was preferred over newer rices with less aroma and with longer grains in both raw and suman forms.